Large scale dog population demography, dog management and bite risk factors analysis: A crucial step towards rabies control in Cambodia. - Véronique Chevalier; Holl Davun; Sopheak Sorn; Pitou Ly; Vutha Pov; Sowath Ly (PLoS ONE, 2021)
Cambodia is a rabid-endemic country. However, data on dog population characteristics are lacking, and there is no national dog vaccination program. We implemented the first extensive door-to-door longitudinal survey in 2 Cambodian provinces, namely Kandal and Battambang, to estimate dog population demographic parameters, identify dog ownership determinants, analyze dog management practices and estimate the yearly cumulative bite incidence and associated factors. During the first session, more than 5000 dogs were recorded and identified. Data on families, dogs and cats characteristics, as well as the number of bites experienced the year before in the family, were recorded. One year later, a second session was performed in both provinces to record missing dogs and the reasons for missing. Age-specific survival rates of the dog populations were computed using Kaplan-Meier estimates. Ownership determinants and bite risk factors were identified using a negative binomial regression model. Dog trade and dog meat consumption were often reported. We estimated high dog-to-human ratios (1:3.8 in Kandal, and 1:3.3 in Battambang). The mean age of dog populations was 26.4 months in Kandal against 24.3 in Battambang, with a survival rate of 52% at 24 months in Kandal (34% only in Battambang). They were no feral dogs, but the large majority of recorded dogs were free roaming. In both provinces, the number of dogs significantly increased in families with children younger than 15, and when the head of the family was a male. The estimated yearly cumulative bite incidences were 2.3 and 3.1% in Kandal and Battambang provinces respectively, and are among the highest in the world. Our survey provides valuable data to focus information programs, parametrize transmission models and identify efficient vaccination strategies to control rabies in Cambodia in the future.